NEEDS ANALYSIS FOR LEARNING RESOURCE - Rr. Sri Kartikowati; Gimin Gimin (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
This research aims to analyze the needs and the use of learning resources by lecturers in the Economic Theory and Policy course since it has been investigated that the majority of students have low learning motivation. The learning motivation itself on the other side can be improved when the learning resource meets the students' needs. 30 students of the Economic Education Magister Program of Riau University were selected as subjects of this explorative research. Data was collected using a questionnaire to be analyzed descriptively and quantitatively using tables and graphs. Findings show that: (1) Some learning resources are frequently used for most of the students by lecturers in their lecture (lecturers’ explanations in class, group discussions), digital books, and powerpoint slides by the aid of high-performance computer; (2) Some learning resources are preferred by most students; yet have not been used by the lecturers namely: digital clippings, exercises, and interactive quizzes; (3) Services provided by the institution, namely: internet/wi-fi facility, convenient and complete facilities of the library; comfortable classrooms, and beautiful parks surrounding the learning area, have to be better improved to perfection; and (4) Some obstacles are met by students during their lecturers, namely: abundant amount of material, fast explanation by lecturers, unreliable internet facility, uncomfortable classrooms, and lack of lecturers' feedback upon assignment. In an attempt to meet the students' needs, a learning strategy is required particularly for utilizing such learning resources as digital books, clippings, and powerpoint slides either offline or online.